2016
DOI: 10.1007/s40093-016-0145-3
|View full text |Cite
|
Sign up to set email alerts
|

Crop residue degradation by fungi isolated from conservation agriculture fields under rice–wheat system of North-West India

Abstract: Purpose In North West-Indo Gangetic Plains (NW-IGP) of India in situ burning of crop residues is practiced by majority of farmers' which deteriorates soil and environmental quality. Fungi have the potential for lignocellulose degradation and can be used for the in situ decomposition of crop residues. Lignocellulose degrading fungal spp. were isolated and evaluated for the activity of lignocellulolytic enzymes. Method The lignocellulose degrading fungi were isolated by appearance of zone on carboxy methyl cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Microbial enzymes are involved in soil nutrient cycling, and are used to evaluate soil quality (Choudhary et al, 2018). Among soil microbes, fungi are critical components in soil system and are regarded as the primary decomposers in soils, as they secrete various enzymes that breakdown lignocelluloses (Choudhary et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial enzymes are involved in soil nutrient cycling, and are used to evaluate soil quality (Choudhary et al, 2018). Among soil microbes, fungi are critical components in soil system and are regarded as the primary decomposers in soils, as they secrete various enzymes that breakdown lignocelluloses (Choudhary et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…(Bhavsar et al 2011;Moreira et al 2014), Mucor racemosus (Bogar et al 2003b), and Sporotrichum thermophile (Singh andSatyanarayana 2006b, Maurya et al 2017), Thermomyces lanuginosus (Makolomakwa et al 2017), and Rhizopus oryzae (Arora et al 2017) have been reported to produce phytase. Several filamentous fungi and their enzyme products are used to break down the bond between the polysaccharides (cellulose and hemicellulose) and lignin in wheat straw to improve its digestibility through the process referred to as biological-pretreatment (Sindhu et al 2016, Choudhary et al 2016, Bagewadi et al 2017. Many previous studies have also reported the ability of filamentous fungi to produce various commercial enzymes from wheat straw (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Cultured selected isolates in three types of medium were shown a growth rate in decomposed material faster than empty bunches. The effectiveness of biodegradation of lignocellulolytic microbes in different media has been reported in some research such as the activity of cellulase in liquid medium using wheat bran as carbon source (Sorgatto et al 2012), lignocellulolytic activity in solid-state fermentation (Choudhary et al 2016). In the case of oil palm empty fruit bunch decomposition, Shahriarinour et al (2011) reported the effect of different fermentation substrates in the activity of Aspergillus terreus.…”
Section: Collection and Selection Isolatementioning
confidence: 99%